Human milk nutritional composition across lactational stages in Central Africa - Moya-Alvarez, Violeta; Eussen, Simone R. B. M.; Mank, Marko; Koyembi, Jean-Christophe Junior; Nyasenu, Yawo Tufa; Ngaya, Gilles; Mad-Bondo, Daniel; Kongoma, Jean-Bertrand; Stahl, Bernd; Sansonetti, Philippe J.; Bourdet-Sicard, Raphaëlle (Frontiers in Nutrition, 2022)
The African region encompasses the highest undernutrition burden with the highest neonatal and infant mortality rates globally. Under these circumstances, breastfeeding is one of the most effective ways to ensure child health and development. However, evidence on human milk (HM) composition from African women is scarce. This is of special concern, as we have no reference data from HM composition in the context of food insecurity in Africa. Furthermore, data on the evolution of HM across lactational stages in this setting lack as well. In the MITICA study, we conducted a cohort study among 48 Central-African women and their 50 infants to analyze the emergence of gut dysbiosis in infants and describe the mother-infant transmission of microbiota between birth and six months of age. In this context, we assessed nutritional components in HM of 48 lactating women in Central Africa through five sampling times from week 1 after birth until week 25. Unexpectedly, HM-type III (Secretor + and Lewis genes -) was predominant in HM from Central African women, and some nutrients differed significantly among HM-types. While lactose concentration increased across lactation periods, fatty acid concentration did not vary significantly. The overall median level of 16 detected individual human milk oligosaccharides (HMOs) (core structures as well as fucosylated and sialylated ones) decreased from 7.3 g/l at week 1 to 3.5 g/l at week 25. The median levels of total amino acids in HM dropped from 12.8 mg/ml at week 1 to 7.4 mg/ml at week 25. In contrast, specific free amino acids increased between month 1 and month 3 of lactation, e.g. free glutamic acid, glutamine, aspartic acid, and serine. In conclusion, HM-type distribution and certain nutrients differed from Western mother HM.